Periodic Bedrock Ridges at the ExoMars 2022 Landing Site: Evidence for a Changing Wind Regime. Issue 4 (22nd February 2021) - Silvestro, S.; Pacifici, A.; Salese, F.; Vaz, D.A.; Neesemann, A.; Tirsch, D.; Popa, C.I.; Pajola, M.; Franzese, G.; Mongelluzzo, G.; Ruggeri, A.C.; Cozzolino, F.; et al.
Abstract: Wind‐formed features are abundant in Oxia Planum (Mars), the landing site of the 2022 ExoMars mission, which shows geological evidence for a past wet environment. Studies of aeolian bedforms at the landing site were focused on assessing the risk for rover trafficability, however their potential in recording climatic fluctuations has not been explored. Here we show that the landing site experienced multiple climatic changes in the Amazonian, which are recorded by an intriguing set of ridges that we interpret as Periodic Bedrock Ridges (PBRs). Clues for a PBR origin result from ridge regularity, defect terminations, and the presence of preserved megaripples detaching from the PBRs. PBR orientation differs from superimposed transverse aeolian ridges pointing toward a major change in wind regime. Our results provide constrains on PBR formation mechanisms and offer indications on paleo winds that will be crucial for understanding the landing site geology. Plain Language Summary: Oxia Planum on Mars is the landing site for the ExoMars 2022 mission. The region likely hosted a standing body of water, but the effect of the wind was also important in shaping the landscape. In this study, we first describe a set of linear ridges that, in our interpretation, were sculpted by the wind in a more recent past. We also show that the wind that formed the ridges (Periodic Bedrock Ridges) was blowing from a different direction than the ones that formed younger ripples on top, suggesting a complex geological history of wind erosion and deposition that will be further investigated during the ExoMars mission. Key Points: We present the first evidence for a periodic bedrock ridge (PBRs) pattern from the ExoMars 2022 landing site Formative paleowind directions are extrapolated from PBRs and transverse aeolian ridges Evidence for an Amazonian change in the wind regime are provided